Reliability-based robust design of smart sensing systems for failure diagnostics using piezoelectric materials. (August 2015) - Wang, Pingfeng; Wang, Zequn; Youn, Byeng D.; Lee, Soobum
Highlights: Developed a new method for piezoelectric materials based sensing systems design. Developed a quantitative detectability measure to evaluate the sensing performance. Developed a novel detectability analysis approach based on Mahalanobis distance. Considered uncertainties in structure material properties and operating conditions. Employed two engineering case studies to demonstrate the methodology. Abstract: This paper presents a reliability-based robust design approach to develop piezoelectric materials based structural sensing systems for failure diagnostics and prognostics. A detectability measure is defined to evaluate the performance of any given sensing system, and the sensing system design problem can be formulated to maximize detectability for different failure modes by optimally allocating piezoelectric materials into a target structure. This formulation can be conveniently solved within a reliability-based robust design framework to ensure design robustness while considering the uncertainties such as those from structure properties and operation conditions. Two case studies, that design sensor networks for an aircraft wing panel and a power transformer structure, are employed to demonstrate the effectiveness of the proposed methodology in developing multifunctional material sensing systems.